Disparity in Diabetes Risk Across Native Hawaiians and Different Asian Groups: The Multiethnic Cohort. (May 2015) - Maskarinec, Gertraud; Jacobs, Simone; Morimoto, Yukiko; Chock, Marci; Grandinetti, Andrew; Kolonel, Laurence N.
We evaluated the impact of body mass index (BMI) and lifestyle risk factors on ethnic disparity in diabetes incidence among 89 198 Asian, Native Hawaiian, and white participants of the Multiethnic Cohort who completed multiple questionnaires. After 12 years of follow-up, 11 218 new cases were identified through self-report and health plan linkages. BMI was lowest in Chinese/Koreans, Japanese, and Filipinos (22.4, 23.5, and 23.9 kg/m 2 ). Using Cox regression, the unadjusted hazard ratios were 1.9 (Chinese/Korean), 2.1 (Japanese, Mixed-Asian), 2.2 (Filipino), 2.5 (Native Hawaiian), and 2.6 (part-Asian) as compared with whites. With BMI added, the risk for Japanese, Filipinos, Chinese/Koreans, and mixed-Asians increased (8%-42%) but declined in part-Asians and Native Hawaiians (17%-31%). When lifestyle and dietary factors were also included, the risk was attenuated in all groups (6%-14%). Despite their lower BMI, Asian Americans have a higher diabetes risk than whites, but dietary and lifestyle factors do not account for the excess risk.